Synthesis of ethylbenzene by alkylation of benzene with diethyl carbonate over parent MCM-22 and hydrothermally treated MCM-22 - Li, Yongxin; Xue, Bing; He, Xueyi (Journal of molecular catalysis. A, Chemical, 2009)
MCM-22 hydrothermally treated at 873 K exhibits a great improvement in ethylbenzene selectivity along with a slight decrease in benzene conversion, corresponding to the proper acidity strength of the catalyst. It indicates that alkylation of benzene with diethyl carbonate mainly occurred on Brønsted acid sites, and the effect of Lewis acid sites on the alkylation process was negligible. ▪ Acidity adjustment of MCM-22 was carried out by hydrothermal treatment of parent MCM-22 with flowing pure steam at high temperature. XRD, SEM and N 2 adsorption/desorption results indicated that the crystallinity and pore properties of MCM-22 were affected slightly by hydrothermal treatment at different temperatures. NH 3-TPD and FT-IR with pyridine adsorption showed only a slight decrease in Brønsted acid sites, compared with parent MCM-22, with hydrothermal treatment temperature in the range 773–873 K. The strength of Brønsted acid sites was reduced severely at hydrothermal treatment temperatures of 973 and 1073 K. The Lewis acid sites were only slightly affected by hydrothermal treatment. A substantial improvement in ethylbenzene selectivity along with a slight decrease in benzene conversion was achieved in catalytic synthesis of ethylbenzene by alkylation of benzene with diethyl carbonate over MCM-22 hydrothermally treated at 873 K. A sharp decrease in benzene conversion was detected over MCM-22 hydrothermally treated at 973 K. The results indicate that alkylation of benzene with diethyl carbonate occurred mainly on Brønsted acid sites, and the effect of Lewis acid sites on the alkylation process is negligible. Reduction of Brønsted acid sites of the catalyst can suppress side reactions and improve selectivity for ethylbenzene. It was found that a particular acid strength of catalyst was required to maintain high benzene conversion and ethylbenzene selectivity.